Why People Leave Community Service Organizations: A Mixed Methods Study - Milbourn, Ben; Black, M.; Buchanan, Angus (Springer, 2018)
© 2018 International Society for Third-Sector Research and The Johns Hopkins University Despite the benefits of volunteering to the individual, organization and community, the retention of volunteers within volunteer and not-for-profit organizations remains a significant challenge. Examining the motivations of individuals who have ceased their engagement in a volunteer organization may provide insights to improve retention rates. The perceptions of 64 volunteers formerly involved in an international volunteer organization were examined through community telephone interviews and online surveys. Results show that while volunteers valued their participation in the volunteer organization, their decision to cease engagement in the organization was driven by five major themes: ‘Work overload and burnout,’ ‘Lack of autonomy and voice,’ ‘Alienation and cliques,’ ‘Disconnect between volunteer and organization’ and ‘Lack of faith in leadership.’ Strategies to improve and refine organizational practice and culture may contribute to a strengthened membership and retention.